Combining ability analysis for earliness and yield related characters in pea (Pisum sativum) - RAM, HANUMAN; DHAR, SHRI; CHOUDHARY, H; SHARMA, R K; SOLANKE, A U; PRASAD, PRASAD; TOMAR, B S (The Indian Journal of Agricultural Sciences, 2018)
A study was conducted on the combining ability analysis in a 11×11 half-diallel cross of garden pea (Pisum sativum L.). F1 hybrids (55) along with 11 parental lines were grown in randomized block design with three replications. The mean square due to GCA and SCA were highly significant for all the characters indicating the importance of additive and non-additive genetic components for the characters under study. Further, σ2s was more than σ2g for all the characters suggested the importance of non-additive variance for the improvement of these characters. The parents P2 (GP-17), P5 (GP-473) and P7 (VRP-7) were observed to be good combiners for most characters under study including yield per plant. The crosses P6 × P10, P2 × P8 and P8 × P10 were most promising combinations for total yield per plant. The results indicated the importance of recombinant breeding for effective utilization of non-additive genetic variance in garden pea.